Entre margens, terras e gentes : convivialidades e identidades no sertão do baixo rio São Francisco - Silva, Cícero Bezerra da (2020)
The elaboration of this research has epistemological orientation in the Geography of cultural approach and starts from the assumption that the search for the understanding of spatial relations and spatialities embodies a movement capable of unveiling the lived experiences, as revealing of the geographical reality itself and the senses of being and to be in the world. Thus, the first purpose of the dissertation is to analyze the identity and belonging relationships, considering the conviviality and the revealing knowledge of the geography in the lowlands of the São Francisco River, between the states of Alagoas and Sergipe. For this, it is presented as theoretical support the construction of the place-territory category as a key foundation for understanding the belonging and identities that make the sertanejo riverside “Being”. As for the methodological orientation, we sought to support the qualitative research framework of relational and phenomenal nature, under the assumptions of existential phenomenology of Maurice Merleau-Ponty (1996 [1945]) and the geography of Eric Dardel (2015 [1952]). Among the procedures and instruments of investigation, in turn, stand out the bibliographic research and the work / fieldwork. In the research, directed observation and semi-structured interviews were conducted with a script outlined by the understanding of ways of life, conviviality and belonging, in spite of the registration of knowledge and doings in the interviewees' timeline, aided by the notebook. and the photographic records. Through this dialogical path, we grasp, in the context of Brazilian social thought, the meanings of backcountry and backcountry on three grounds. In the first, sertão and sertanejo are adjectives that refer to the idea of domination; the second concerns the interior as a space / place of experience, reproduction of life and cultural materialization, and the third corresponds to the abstraction in which the essence is subjectivity. As for the multiplicity of identities, they are strongly associated with the historical process of rooting in / for the place, as well as the relations of belonging and the social, environmental and cultural transformations to which the river and its people were submitted, especially after the second half of the century 20th century. In the research, the analysis of identities was conducted based on the classification of Bassand (1989) and Almeida (2008a, 2008b) on which five identity typologies were designated: i. Apathetic and resigned; ii. Potential migrants; iii. Modernists; iv. Traditionalists and v. Regionalists. The construction of the sertanejo riverside being observed, therefore, the amalgam between nature and culture as a living expression of the identities in which the São Francisco river and the sertão (s) form a continuum of materiality and subjectivity, of being notonly riverside, but also to be sertanejo of / in the São Francisco river.